Thematic Analysis of the Hadith ‘Innamā al-Bay’ ‘an Tarāḍin’ on Vending Machine Transactions within the Framework of Hadith al-Ahkam - M. Abdul Aziz; Mohammad Anton Athoillah; Latief Awaludin (Diroyah : Jurnal Studi Ilmu Hadis, 2025)
Abstract : In this contemporary era, the development of Artificial Intelligence (AI) technology has brought significant changes to economic transaction patterns, ranging from electronic commerce systems to digital financial services. One prominent example is the vending machine. A vending machine is an automated device commonly found in various countries, including Indonesia, particularly in public areas. In its operation, the buyer does not directly interact with the seller but simply inserts a certain amount of money into the machine. The presence of AI-driven automation raises several ethical and legal questions, particularly concerning the principle of mutual consent (tarāḍī), which is a fundamental requirement for a valid sale, as stated in the Hadith al-Aḥkām: “Innamā al-bay‘‘an tarāḍin”. This article aims to examine the relevance of this hadith to AI-based transactional practices through a thematic (mawḍū‘ī) approach. The research employs a qualitative method using library research, analyzing classical and contemporary literature on Hadith al-Aḥkām and current scholarly works within the context of modern Islamic discourse. The findings indicate that although AI-mediated transactions operate automatically, the principle of mutual consent can still be fulfilled as long as there is prior agreement, transparency of information, and fairness between the contracting parties. Hence, the hadith provides a normative foundation that the validity of a transaction does not depend on direct human involvement in every stage, but rather on the mutual satisfaction (riḍā) of both parties bound by the contract. Keywords: Hadith al-Aḥkām, contract (‘aqd), vending machine.